Our Way to Home: An Exploratory Study of Pasifika Gay Men in New Zealand, Their Lived Experience and Their Navigation of Sexual Orientation Related Legislative Change - Katavake-McGrath, Filipo (Auckland University of Technology, 2021)
Gay men are an uncounted and silenced group of people within communities of Pacific Island diaspora in New Zealand. The silence emanates from histories of deeply conservative social regulation dominated by Christian organisations that grew from the religious colonisation of the Pacific region in the 1800s. With the first mass migrations of Pacific people to New Zealand in the 1950s, Pacific Christian churches in New Zealand were established to become centres where communities practised heritage languages and cultural traditions. In Pacific families, worldviews were practised founded on the va, representing the sacredness of the relationship between one person and another. The va is central to relationship maintenance as a core component of being of a Pacific ethnicity. People in Pacific ethnic groups saw service to family and community as the best way to maintain relationships and their sacredness. Since the 1980s, Pacific communities in New Zealand have grappled with increasing normalisation and legitimisation of gay men in wider society. Social change was marked by the passing of the Homosexual Law Reform Act in 1986, the Human Rights Act in 1993, the Civil Union Act in 2004 and the Marriage (Definition of Marriage) Amendment Act in 2013. Pacific church teachings condemning homosexuality were challenged by this change, and during times of public interest, Pacific church leaders and other notable community leaders, including celebrities and sportsmen, have publicly campaigned for continued condemnation of homosexuals. This qualitative hermeneutic study follows the Kakala Research Methodology to explore the lived experience of Pacific gay men of these worldviews, traditions, practices, and relevant institutions. It follows Pacific gay men’s attempts to make sense of Pacific worldviews of service to family and community alongside the hurt that resulted from public campaigns of hostility. The main findings of this study were that Pacific people saw themselves as concerned for and protecting the wellbeing of families, based on the va. For some gay men, that protection was extended to them, and for others, the teachings of churches led to hostility. In contrast to the care and relationships in the Pacific families, church teachings were reliant on; the Bible as an authoritative and unique source of teaching, and the authority and power of the church minister. Based on church teachings, some Pacific gay men were; exposed to marginalisation in the family, protests in public domains and campaigning by church ministers to influence parliament in opposition to marriage equality legislation. This study explores that hostility and questions the authenticity of the structures that sat behind it. It also explores the strength of Pacific families and worldviews to understand the protective factors that offered support to Pacific gay men. Its findings make contributions to studies of Pacific peoples, Pacific ethnic cultural groups, LGBTI people in New Zealand and public policy.
Keywords: Select committee; Private members bill; Marriage equality; Pacific; Gay; LGBTI; Homophobia; Church; Folau; Kakala; Talanoa; Marginalisation; Racism; Dawn raid